Large Small Submodules with Chain Conditions - Ibrahim, Rawnaq Kh.; Yassen, Sahira M. (Iraqi Journal of Science, 2026)
We consider R is any ring with identity and  is a non-zero unitary left R-module. In this article we study the notions of large small submodules with ascending (descending) chain conditions on large small submodules. Also, we will discuss and study many basic properties about this concept that fulfills the chain condition with its generalization to the ring. Where a submodule  of  is said to be large small of  denoted by if for  such that  then  is essential in .